A Study of Parameters Affecting Wear Resistance of Alumina and Yttria Stabilized Zirconia Composite Coatings on Al-6061 Substrate. (31st December 2012) - Krishnamurthy, N.; Prashanthareddy, M. S.; Raju, H. P.; Manohar, H. S.
Abstract : In this investigation, a composite coating of alumina and yttria stabilized zirconia in equal proportion was developed on Al-6061 substrate using Atmospheric Plasma Spraying technique. Two commercially available powders of chemical composition Al 25Fe7Cr5Ni and Al2 O3 30(Ni 20Al) were used as bond coats. The coating samples were subjected to abrasive wear test as per ASTM G99. From the results it was found that wear rate and coefficient of friction depend on various parameters such as microstructure, surface roughness, porosity, coating thickness, and hardness. It was also found that the mechanism of wear is mainly due to abrasion and once the bond coat is exposed to the disc, it loses material by adhesion. As the coating systems possess α -Al2 O3 and ZrO2, they can be used for wear and heat resistant applications such as cylinder liner of internal combustion engines.